A continuous flow approach for the C–H functionalization of 1, 2, 3-triazoles in γ-valerolactone as a biomass-derived medium. Issue 12 (4th June 2018) - Ferlin, Francesco; Luciani, Lorenzo; Santoro, Stefano; Marrocchi, Assunta; Lanari, Daniela; Bechtoldt, Alexander; Ackermann, Lutz; Vaccaro, Luigi
Abstract : Herein we report an efficient procedure for the C–H functionalization of 1, 2, 3-triazoles in a continuous flow regime applied to a variety of functionalities and to the inter- or intramolecular versions of the process. Abstract : Herein we report an efficient procedure for the C–H functionalization of 1, 2, 3-triazoles in a continuous flow regime applied to a variety of functionalities and to the inter- or intramolecular versions of the process. The continuous-flow protocol is based on the use of a heterogeneous catalyst (Pd/C), a soluble organic base and GVL as the reaction medium. Flow conditions allow an optimal recovery/reuse and durability of the catalyst, which combined with the simple purification of the products and the recovery of the reaction medium make the proposed protocol operationally simple and very efficient in terms of waste minimization as proven by low metal leaching and a low associated E -factor.